1962
DOI: 10.1161/01.cir.26.5.841
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Atherosclerosis

Abstract: In order to complete the fragmentary knowledge of the natural history of atherosclerosis, the authors examined the coronary arteries of 403 captive and 146 wild vertebrates living in freedom, as well as the aortas of 134 of them. In 88 of the captive animals and in 51 of the free individuals, lipidogram, total cholesterol, beta-cholesterol and cholesterol/phospholipid ratio were also determined. In this material, spontaneous atherosclerosis always developed in arteries already impaired by intimal scl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1963
1963
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Fibrinolytic activity is present in the central layers (media and intima) of veins, thus confirming observations on human material 21 ' 23 and in dog. 28 The results also confirm previous observations on differences in the patterns of arteries and veins. Data on the pulmonary artery and vein show marked differences in distribution of fibrinolytic activity (low in intima of pulmonary artery but high in pulmonary vein).…”
supporting
confidence: 90%
“…Fibrinolytic activity is present in the central layers (media and intima) of veins, thus confirming observations on human material 21 ' 23 and in dog. 28 The results also confirm previous observations on differences in the patterns of arteries and veins. Data on the pulmonary artery and vein show marked differences in distribution of fibrinolytic activity (low in intima of pulmonary artery but high in pulmonary vein).…”
supporting
confidence: 90%
“…More recently, Vastesaeger & Delcourt (1962) recorded that the coronary arteries of a large Anaconda (Eimectes inurinus) showed fragmentation of the internal elastica and slight fibrous thickening of the intima; and a Nile crocodile (Crocodilus niloticus) also showed focal intimal thickening with rupture of the internal elastic membrane of a main coronary trunk. In the latter case, the presence of vacuolated histiocytes in the lesions suggested, to the authors, a diagnosis of atherosclerosis although, in a subsequent report, Vastesaeger, Vercruysse & Delcourt (1963) made no mention of the occurrence of coronary atherosclerosis in 38 reptiles examined.…”
Section: Reptilesmentioning
confidence: 99%
“…In 1962 Vastesaeger and Delcourt observed the presence of lipid-rich atherosclerosis-like lesions in the aorta of a tuna( Thunnus thynnus )4. More recently, Seierstad et al demonstrated similar lesions in coronary arteries of farmed Atlantic salmon ( Salmo salar )5.…”
Section: Introductionmentioning
confidence: 99%